Serbia and Montenegro : First Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Serbia and Montenegro's First Review Under the Extended Arrangement (EA). Serbia and Montenegro's economic and policy performance has remained good under the current EA, but daunting challenges lie ahead. Macroeconomic policies need to be carefully calibrated to address potential risks to macroeconomic and financial instability, while the task of economic restructuring will be increasingly difficult. The IMF staff welcomes the authorities' commitment to address delays in the adoption of reform legislation that led to nonobservance of some structural benchmarks and notes the need to avoid new slippages.